The influence of bone mineral density and cortical index on the complexity of fractures of the proximal humerus - den Teuling, J.W.A.M. (Bone Joint Res, 2017)
OBJECTIVES: The goal of this study is to investigate the relation between indicators of osteoporosis (i.e., bone mineral density (BMD), and Cortical Index (CI)) and the complexity of a fracture of the proximal humerus as a result of a low-energy trauma. METHODS: A retrospective chart review of 168 patients (mean age 67.2 years, range 51 to 88.7) with a fracture of the proximal humerus between 2007 and 2011, whose BMD was assessed at the Fracture Liaison Service with Dual Energy X-ray Absorptiometry (DXA) measurements of the hip, femoral neck (FN) and/or lumbar spine (LS), and whose CI and complexity of fracture were assessed on plain anteroposterior radiographs of the proximal humerus. RESULTS: No significant differences were found between simple and complex fractures of the proximal humerus in the BMD of the hip, FN or LS (all p > 0.3) or in the CI (p = 0.14). Only the body mass index was significantly higher in patients with a complex fracture compared with those with a simple fracture (26.9 vs 25.2; p = 0.05). CONCLUSION: There was no difference in BMD of the hip, FN, LS or CI of the proximal humerus in simple compared with complex fractures of the proximal humerus after a low-energy trauma. Factors other than the BMD and CI, for example body mass index, may play a more important role in the complexity of this fracture. Cite this article: J.W.A.M. den Teuling, B.S. Pauwels, L. Janssen, C.E. Wyers, H. M. J. Janzing, J.P.W. van den Bergh, J. W. Morrenhof. The Influence of bone mineral density and cortical index on the complexity of fractures of the proximal humerus. Bone Joint Res 2017;6:584–589. DOI: 10.1302/2046-3758.610.BJR-2017-0080.